2014
DOI: 10.1080/00908320.2014.898926
|View full text |Cite
|
Sign up to set email alerts
|

Marine Renewable Energies: Opportunities, Law, and Management

Abstract: Marine renewable energies are still at a very incipient stage. Even so, it can be anticipated that if such energies were to be developed, multiple benefits could be achieved in the environmental, social, and economic spheres. However, these benefits are not without possible controversial aspects. This article examines the content and scope of the applicable international law of the sea regarding the use of renewable energy from the seas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…In view of the increasingly sharp contradiction between marine economic and social development and marine ecological protection, scholars all over the world pay much attention to their coordinated development at the end of the 20th century, especially in the 21st century. Research topics mainly cover the marine economic transformation of coastal countries and regions (zones) (Liu et al, 2012;Delgado et al, 2021), marine fishery management (Bundy et al, 2017;Gelcich et al, 2019), marine environment governance (Parlee and Wiber, 2018;Devenport et al, 2021), marine protected area management (Carcamo and Gaymer, 2013;Jones et al, 2013), marine biodiversity restoration (Lockwood et al, 2012;Jacob et al, 2018), and marine energy utilization (Castelos, 2014;Goffetti et al, 2018), among others. For example, Sarker et al (2018) analyzed the sustainable development potential of the marine economy in Bangladesh; Voyer et al (2020) took Timor-Leste as an example for assessing consistency and coordination between policies and marine economic development; Gerhardinger et al (2020) formulated a transformation experiment of sustainable development for the marine economy in Brazil; Costello et al (2012) suggested specific plans for the repair, reconstruction, and income increase of small-scale fisheries in the world that did not undergo assessment; lastly, Vince and Hardesty.…”
Section: Marine Ecoeconomic Systemmentioning
confidence: 99%
“…In view of the increasingly sharp contradiction between marine economic and social development and marine ecological protection, scholars all over the world pay much attention to their coordinated development at the end of the 20th century, especially in the 21st century. Research topics mainly cover the marine economic transformation of coastal countries and regions (zones) (Liu et al, 2012;Delgado et al, 2021), marine fishery management (Bundy et al, 2017;Gelcich et al, 2019), marine environment governance (Parlee and Wiber, 2018;Devenport et al, 2021), marine protected area management (Carcamo and Gaymer, 2013;Jones et al, 2013), marine biodiversity restoration (Lockwood et al, 2012;Jacob et al, 2018), and marine energy utilization (Castelos, 2014;Goffetti et al, 2018), among others. For example, Sarker et al (2018) analyzed the sustainable development potential of the marine economy in Bangladesh; Voyer et al (2020) took Timor-Leste as an example for assessing consistency and coordination between policies and marine economic development; Gerhardinger et al (2020) formulated a transformation experiment of sustainable development for the marine economy in Brazil; Costello et al (2012) suggested specific plans for the repair, reconstruction, and income increase of small-scale fisheries in the world that did not undergo assessment; lastly, Vince and Hardesty.…”
Section: Marine Ecoeconomic Systemmentioning
confidence: 99%
“…Likewise, as innovative technologies which constitute a sustainable and modern source of renewable energy that can also become an opportunity for economic growth and the creation of new jobs (O 'Hagan, 2015), OREs can help reach the sustainable Goals 7 (to "ensure access to affordable, reliable, sustainable, and modern energy for all"), 8 (to "Promote sustained, inclusive and sustainable economic growth, full and productive employment, and decent work for all"), and 9 (To "Build resilient infrastructure, promote sustainable industrialization, and foster innovation") of this Agenda. As scholars highlighted (e.g., Abad, 2014a), OREs are closely linked to the Principle of Sustainable Development, which can be defined, by inspiration in the 1987 Brundtland Report, as lasting development aimed at meeting the human needs of both present and future generations. In this sense, the transition from conventional energy sources to inexhaustible energy sources, such as those generated by currents, tides, or waves, can contribute to cover the energy needs of coming generations through the utilization of inexhaustible resources and better correspond to the contemporary environmental challenges.…”
Section: Endnotesmentioning
confidence: 99%
“…The concept of BE refers to the capacity of exploiting MREs. MRE, as affirmed by Castelos [3], is "a form of renewable energy deriving from the various natural processes that take place in the marine environment". Thus, technologies that convert kinetic and chemical potentials or thermal properties of seawater are involved in the definition of BE.…”
Section: Definition and Categorization Of Blue Energy (Be)mentioning
confidence: 99%